Klio : Beiträge zur Alten Geschichte (De Gruyter (A), 1901)
Klio is one the oldest journal in the German Altertumswissenschaften. It publishes articles on the history of ancient Greece and Rome, including their relations to the ancient Near East, and also covers specialist areas such as epigraphy, papyrology, archaeology, and numismatics. Brief book reviews provide an overview of the latest publications in the field.